Immunization with Complete Freund’s Adjuvant Reveals Trained Immunity-like Features in A/J Mice - Kiruthiga Mone; Shraddha Singh; Fatema Abdullatif; Meghna Sur; Mahima T. Rasquinha; Javier Seravalli; Denise K. Zinniel; Indranil Mukhopadhyay; Raul G. Barletta; Teklab Gebregiworgis; Jay Reddy (Vaccines)
Background/Objectives: Freund’s adjuvants induce different immunomodulatory effects, but their underlying molecular mechanisms are unclear. In this study, we investigated whether the immune-stimulating effects of the complete Freund’s adjuvant (CFA) involve the mechanisms of trained immunity (TI). Methods: We examined bone marrow cells (BMCs) isolated from CFA-immunized A/J mice to address this question. Incomplete Freund’s adjuvant (IFA) and Mycobacterium tuberculosis var. bovis Bacillus Calmette-Guérin (BCG) served as negative and positive controls, respectively. We evaluated cytokine profiles, metabolic, and epigenetic changes. Results: First, BMCs from all groups except saline showed varied levels of IL-1β, IL-6, and TNF-α. But expression of CCL5 and CXCL10 was significantly elevated only in the CFA and BCG groups. Transcriptionally, significant elevations were noted for TNF-α and IL-1β in the CFA and BCG groups, whereas CXCL10, IL-6, and IL-10 were upregulated in the CFA and BCG groups, respectively. Second, while BMCs from the BCG group expressed the markers of both the M1 and M2 macrophages, no clear trends were noted in the CFA and IFA groups. Third, cell lysates from the CFA group revealed metabolic reprogramming in the BMCs. Specifically, we observed an increased level of lactate, indicative of aerobic glycolysis, which is implicated in TI, and this was also detected in the IFA group. Fourth, epigenetic analysis revealed histone enrichment in the promoter region of TNF-α, in the CFA group, but to a lesser degree than the BCG group. However, no epigenetic changes were observed in the IFA group. Conclusions: Our data provide new insights into the mechanisms of Freund’s adjuvants and the immunomodulatory effects of CFA could involve the features of TI.